Legal fictions as ideological source of law - Elena V. Abramova (Правоприменение)
The subject. The article studies legal fictions from the point of view of their correlation with ideological sources of law.The purpose of the article is to confirm or disprove hypothesis that legal fictions may be described as one of the ideological sources of law.The methodological basis for the study includes analysis and synthesis, interpretation of legal literature.Results, scope of application. Legal fictions are legal provisions enshrined in the text of regulatory legal acts in the form of separate regulatory regulations. They play an important role in lawmaking and in the mechanism of legal regulation. Fictions perform the function of protecting various interests and the function of procedural economy, contribute to the rapid and correct resolution of the case on the merits, have the necessary impact on the participants of the proceedings.Legal fictions have their own set of features. They are characterized by a) the deliberate falsity of the assumption; b) this assumption is legally irrefutable, the possibility of proving the opposite is excluded; c) the assumption is legal. provided for in regulatory legal acts; d) assumption, which is given the importance of legal facts.The ideological significance of legal fictions as sources of law is manifested in the fact that they are associated with legal norms, in the content of many of them; this is a special kind of legal norm, in the content of which there is a certain fiction; fictions are one of the means of formalization of normative material and simplification of the structure of actual compositions. Legal fictions are widely used in the gaps in the law, are one of the ways to effectively fill them.Legal fictions bring clarity to the legal regulation of public relations, being a necessary part of legal regulation. Fictions participate in legal regulation in two forms (types): through theoretical and practical (normative) constructions. Theoretical fictions, being a part of the legal doctrine, act as independent regulators (for example, constructions of the legal entity, the state, etc.). Legal fictions perform certain functions. They eliminate the uncertainty in the legal regulation; they help to simplify legal relations and make legal regulation stable and stable; they help to translate everyday reality into legal reality; they help to simplify legal relations and make legal regulation stable and stable.Conclusions. Legal fiction can be considered an ideological source of law, if we consider it as a legal fact, its variety. But this characteristic is not prevailing among other significant properties of legal fictions.